A comparative cross sectional study on the knowledge, attitude and practice of the community based rehabilitation programme for children with special needs in the district of Kota Bharu, Kelantan, 1998 - Nik Rubiah Nik Abdul Rashid,; Khadijah Shamsuddin, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A comparative cross sectional study was conducted on the knowledge, attitude and practice (KAP) of the community towards community based rehabilitation (CBR) programme for children with special needs in the district of Kota Bharu, Kelantan in September 1998. The study samples comprised of 150 respondents from Wakaf Che Yeh Health Centre where CBR programme was available and 150 respondents from Pengkalan Cepa Health Centre where there was no CBR programme. The respondents aged between 18 years to 64 years old. Comparison of the KAP of these two communities is important to improve the CBR programme whereby community participation is an important component. Positive knowledge and attitude as well as active community participation in the CBR programme will ensure the effectiveness and sustainability of the programme. Pretested guided questionnaires were used to measure the KAP of the community towards CBR programme. The hypothesis of the study was that the KAP of the community where CBR programme was available was better than the KAP of the community without the CBR programme. The study revealed that there was significant relationship between the knowledge, attitude and practice of the communities in the two study areas (p<0.05). It was found that knowledge and attitude of respondents in area without CBR was better than that of respondents in area with CBR. However participation in activities for the handicap was better among respondents in area with CBR. Multivariate analysis revealed that the existence or non-existence of CBR programme does not affect the knowledge, attitude and practice of the community (p>0.05). However, risk factors for low knowledge and negative attitudes on CBR were low educational status, housewife and absence of car; women have less negative attitudes toward CBR for children with special needs compared to men. These differences are statistically significant. After controlling for all the other factors it was found that being married is a risk factor for low involvement in rehabilitation activities, where as those with low educational status and having contact with the handicapped were found to be .protective. These differences are statistically significant. Based on these findings, it 1: is hoped that the knowledge, .attitude and community participation in CBR programme for children with Special needs can be further Improved and enhanced by f special emphasis on these positive predictive risk factors.